Design of H-Tree fractal slots frequency reconfigurable hexagonal patch antenna using PIN diodes. Issue 12 (13th August 2019) - Fadamiro, Akinwale O.; Famoriji, Oluwole J.; Zakariyya, Rabiu Sale; Zhang, Zhongxiang; Lin, Fujiang
ABSTRACT: In this paper, a frequency reconfigurable hexagonal patch antenna with the ability to operate in L and S bands is been presented. This patch incorporates a H-Tree fractal slot on the patch and ground plane of the resonating element with five (5) PIN diodes integrated on the antenna surface to change the current distribution which consequently changes the resonance frequency under different conditions of switches, thereby making it a frequency reconfigurable antenna. The proposed patch antenna allows reconfigurable switching in multiple frequency bands between 1 and 3 GHz, with relative narrow bandwidths. Computer simulation technology (CST) microwave studio software is used to analyze the design and it's fabricated on a Rogers R4350 substrate (0.508 mm thickness) with an area of 63 mm × 69.75 mm. Both simulation and measurement have shown good agreements with each other, satisfying the requirements for Bluetooth, GSM and WLAN antenna applications.